CUÁLES SON LOS PRINCIPIOS DEONTOLÓGICOS DEL PERIODISMO DIGITAL? - SAA TABARA, FERNANDO STWAR (2024)
Through the Internet, people have been able to communicate and find out about almost all events at the local, national and international level, almost immediately, however, this immediate is not always one hundred percent verified, the information spreads unimaginable, since the sources are not verified, the principles to which the journalistic profession is subject are put at risk. But apparently today, the search to generate more followers is something insignificant for those who do not abide by a deontological standard. In this thesis study, the deontological codes of digital journalism are presented as a central axis, objectives are addressed such as determining their importance, analyzing their application in the journalistic context, identifying their effects to know how they should be managed in the professional area and subsequently . propose a solution to the lack of these ethical principles, if necessary. To effectively carry out the study, it was decided to carry out interviews with five different media outlets that are located in the Province of Los Ríos. It is worth mentioning that these communication entities are already officially registered in the RPM, which further validates the information provided by its managers. The conversation with each of the respective selected members was born because the essence of the system is in decline.